Power, Policy, and Citizen Participation in Santo André, Brazil. (March 2017) - Albert, Victor
City master plans assumed a central role in urban planning in Brazil with the promulgation of a new constitution in 1988 and the passage of enacting legislation in 2001. Citizen participation became an important part of this new urban planning framework. In contrast to some of Brazil's other democratic experiments, participation in urban planning has been received critically or with only cautious optimism. A comparison of two participatory forums in Santo André, São Paulo, shows that established patterns of administrative power can decisively influence the participation of the public in city planning. Differences in the executive structures of the two institutions enabled one of them but not the other to foster open-ended deliberation on policies with members of disadvantaged groups. The study suggests that participation might be enhanced by reserving executive positions for civil society participants, including the public at all stages of policy development, choosing participants largely from disadvantaged groups, and keeping the forum small. Planos diretores para cidades desempenharam papel fundamental no planejamento urbano brasileiro com a promulgação da Constituição de 1988 e o sancionamento da legislação em 2001. Demais, a participação de cidadãos tornou-se importante elemento dessa nova moldura de planejamento urbanístico. Ainda assim, em contraste com outros experimentos democráticos no Brasil, a participação no planejamento urbano tem sido recebida de maneira crítica ou no máximo com otimismo cauteloso. Contudo, uma comparação entre dois forums participativos em Santo André, São Paulo, demonstra que padrões estabelecidos de poder administrativo tiveram influência decisiva na participação pública no planejamento urbano. Diferenças na estrutura executiva das duas instituições permitiram que uma delas, mas não a outra, promovesse deliberações transparentes sobre iniciativas enquanto permitia a participação de grupos menos privilegiados. O estudo sugere que a participação pode ser ampliada com a nomeação de participantes da sociedade civil a cargos executivos, incluindo-se o público em todos os estágios da política de desenvolvimento e escolhendo-se indivíduos majoritariamente entre segmentos mais desfavorecidos da população. O forum deve, ainda, manter-se pequeno.